Outcomes after bloodstream infection in hospitalized pediatric hematology/oncology and stem cell transplant patients. Issue 12 (5th September 2019) - Dandoy, Christopher E.; Kelley, Tammy; Gaur, Aditya H.; Nagarajan, Rajaram; Demmel, Kathy; Alonso, Priscila Badia; Guinipero, Terri; Savelli, Stephanie; Hakim, Hana; Owings, Angie; Myers, Kasiani; Aquino, Victor; et al.
Abstract: Background: Pediatric hematology/oncology (PHO) patients receiving therapy or undergoing hematopoietic stem cell transplantation (HSCT) often require a central line and are at risk for bloodstream infections (BSI). There are limited data describing outcomes of BSI in PHO and HSCT patients. Methods: This is a multicenter ( n  = 17) retrospective analysis of outcomes of patients who developed a BSI. Centers involved participated in a quality improvement collaborative referred to as the Childhood Cancer and Blood Disorder Network within the Children's Hospital Association. The main outcome measures were all‐cause mortality at 3, 10, and 30 days after positive culture date; transfer to the intensive care unit (ICU) within 48 hours of positive culture; and central line removal within seven days of the positive blood culture. Results: Nine hundred fifty‐seven BSI were included in the analysis. Three hundred fifty‐four BSI (37%) were associated with at least one adverse outcome. All‐cause mortality was 1% ( n  = 9), 3% ( n  = 26), and 6% ( n  = 57) at 3, 10, and 30 days after BSI, respectively. In the 165 BSI (17%) associated with admission to the ICU, the median ICU stay was four days (IQR 2‐10). Twenty‐one percent of all infections ( n  = 203) were associated with central line removal within seven days of positive blood culture. Conclusions: BSI in PHO and HSCT patients are associated with adverse outcomes. These data will assist in defining the impact of BSI in this population and demonstrate the need for quality improvement and research efforts to decrease them.